THE EFFICACY OF PLASMA EXCHANGE IN COVID-19 PATIENTS WITH COMORBID DIABETES MELLITUS: Plasma Exchange Efficacy in COVID-19 Patients - Arshad, Komal; ., Zill-e-Humayun; Kamran, Sultan Mehmood; Khaliq, Ikram; Asif, Muhammad Raza; Tanveer, Saman (Pakistan Armed Forces Medical Journal, 2021)
Objective: To explore the use of therapeutic plasma exchange as adjunctive therapy in COVID-19 patients with and without diabetes mellitus.Study Design: Prospective, observational study.Place and Duration of Study: Pakistan Emirates Military Hospital Rawalpindi, from Jan to Feb 2021.Methodology: A total of 90 male patients with laboratory-confirmed coronavirus infection were selected based on our inclusion criteria and their management and outcomes were recorded. The data were analyzed using SPSS-22 and Microsoft Excel.Results: The mortality rate was lower in patients who received 1 or more sessions of plasma exchange compared to those who did not receive plasma exchange (7.5% vs 12%). A lower mortality rate was seen in patients without diabetes who received therapeutic plasma exchange in addition to standard therapy compared to patients who received standard therapy alone (0 vs 14.82%, p=0.112). In patients with diabetes, a higher mortality rate was found in the group that had received therapeutic plasma exchange in addition to standard therapy instead of standard therapy alone (20% vs 8.7%, p=0.365).Conclusion: Overall our study supports the use of therapeutic plasma exchange in COVID-19 patients. However, although statistically insignificant, there appears to be a higher mortality rate in patients with diabetes who received therapeutic plasma exchange in addition to standard therapy. As such, we recommend further investigation of this aspect.